Bridge of souls - Schwab, Victoria (Schwab, Victoria. City of ghosts (Series), 2021)
Cassidy Blake travels to New Orleans with her parent's new ghost-hunting show along with her ghost best friend Jacob. She soon becomes enchanted with the ghostly magic of the city and even encounters her friend Lara, a fellow In-betweener. But when a messenger of Death appears, Cassidy must try to stop it before she is taken beyond the Veil.